2017
DOI: 10.1111/jce.13397
|View full text |Cite
|
Sign up to set email alerts
|

How to perform posterior wall isolation in catheter ablation for atrial fibrillation

Abstract: Catheter ablation has become standard of care in patients with symptomatic atrial fibrillation (AF). Although there have been significant advances in our understanding and technology, a substantial proportion of patients have ongoing AF requiring repeat procedures. Pulmonary vein isolation (PVI) is the cornerstone of AF ablation; however, it is less effective in patients with persistent as opposed to paroxysmal atrial fibrillation. Left atrial posterior wall isolation (PWI) is commonly performed as an adjunct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Long‐term AF burden discrepancy implies that in patients with paroxysmal AF, additional extensive ablation of the LA posterior wall in CVP, in contrast to CA, could play a role on the long‐term sinus rhythm maintenance. Some data exist supporting ablation of the embryologically similar PV antra and LA posterior wall as a continuity in the treatment of AF . Moreover, the epicardial lesion pattern utilized in this study has also shown good long‐term outcomes in a mostly persistent AF patient population with 31% and 36% recurrence rates (cutoff of 1% AF burden) after 1 and 4 years of ILR monitoring …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Long‐term AF burden discrepancy implies that in patients with paroxysmal AF, additional extensive ablation of the LA posterior wall in CVP, in contrast to CA, could play a role on the long‐term sinus rhythm maintenance. Some data exist supporting ablation of the embryologically similar PV antra and LA posterior wall as a continuity in the treatment of AF . Moreover, the epicardial lesion pattern utilized in this study has also shown good long‐term outcomes in a mostly persistent AF patient population with 31% and 36% recurrence rates (cutoff of 1% AF burden) after 1 and 4 years of ILR monitoring …”
Section: Discussionmentioning
confidence: 57%
“…16,17 Outcomes, even for paroxysmal AF patients who maintained sinus rhythm off AADs at 1 year, have been shown to decline throughout long-term follow-up. 18,19 [20][21][22] Moreover, the epicardial lesion pattern utilized in this study has also shown good long-term outcomes in a mostly persistent AF patient population with 31% and 36% recurrence rates (cutoff of 1% AF burden) after 1 and 4 years of ILR monitoring. 23 Procedural duration did not differ significantly between both groups, which can be attributed to much shorter duration of the endocardial part of the procedure in the CVP group.…”
Section: Discussionmentioning
confidence: 66%
“…PV isolation was extensively performed in all cases, and 70.4% of RF cases underwent creation of the right posterior wall line adjacent to the left posterior wall line. This method, which is called the touching rings method, can be used to isolate the PV antrum and part of the LA posterior wall (Figure ). After PV isolation, isoproterenol (5‐20 µg/min) was intravenously injected, and atrial burst pacing (140‐240 ms) was performed to induce non‐PV AF foci .…”
Section: Methodsmentioning
confidence: 99%
“…It is those cylinder‐like “veins” that drain into the left atrium. As noted by the authors, embryologically, the pulmonary veins unite to a common antrum that then is resorbed as it meets the primordial left atrium such that the posterior wall is the pulmonary vein along with the cylindrical components draining oxygenated blood from the lungs. Specifically, histologically as well as developmentally, the posterior wall and the vein‐like structures draining are indistinguishable with both components having varying amounts of atrial myocardium wrapping around the primary venous components…”
Section: What Is the Pulmonary Vein?mentioning
confidence: 99%
“…The purpose of the “Techniques, Technology, and Innovation” section in the Journal of Cardiac Electrophysiology is primarily to highlight the methodological details of executing proven effective electrophysiology procedures. A prime example in the present issue is by Sugumar et al . on how to conduct one of the most challenging isolation procedures in our field.…”
Section: Introductionmentioning
confidence: 99%